An Empirical Investigation of International Asset Pricing - Korajczyk, Robert A.; Viallet, Claude J. (Review of Financial Studies, 1989)
We investigate several asset pricing models in an international setting. We use data on a large number of assets traded in the United States, Japan, the United Kingdom, and France. The model together with the hypothesis of capital market integration imply testable restrictions on multivariate regressions relating asset returns to various benchmark portfolios. We find that multifactor models tend to outperform single-index models in both domestic and international forms especially in their ability to explain seasonality in asset returns. We also find that the behavior of the models is affected by change in the regulatory environment in international markets.